Alat Bantu Berjalan Tunanetra Berbasis Mikrokontroler Arduino - Ramdani, Sahrul; Arifin, Muhyiddin Zainul; Sujono, Sujono (KH. A. Wahab Hasbullah University, 2021)
These blind people still have difficulties in carrying out their activities, especially in terms of mobility in society. This is of course due to the lack of facilities and infrastructure that can support blind people in carrying out their daily activities. One of the assistive devices commonly used is a blind cane. With this stick, blind people are quite helped, especially when walking, but the conventional cane has limitations, one of which is the reach is too short. Thus, in this study, a concept for walking aids for blind people was developed by designing a new device that can cover the limitations of conventional canes. The tool is designed to utilize microcontroller technology with a minimum Arduino uno system, ultrasonic sensor HC-SR04, and DFPlayer Mp3 Mini module. The results showed that the designed tool can detect a maximum distance of 80 cm and can make a sound when the ultrasonic sensor is blocked.